Characterization of Sclerotinia sclerotiorum infecting Cucurbita pepo L. in India and its interaction with Trichoderma asperellum - Manjunath, M; Venkataravanappa, V; Tripathi, A N; Rai, A B; Singh, B (Indian Journal of Plant Protection, 2020)
Short Communication